2012 15th International Conference on Computer and Information Technology (ICCIT) 2012
DOI: 10.1109/iccitechn.2012.6509716
|View full text |Cite
|
Sign up to set email alerts
|

New sufficient conditions for Hamiltonian paths

Abstract: A Hamiltonian path in a graph is a path involving all the vertices of the graph. In this paper, we revisit the famous Hamiltonian path problem and present new sufficient conditions for the existence of a Hamiltonian path in a graph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Connections exist only between infills that do not belong to the same sub-polygon (cluster) and are assigned with weights. The Hamiltonian search is basically NP-hard [35]. In the graphs presented, the computation of a Hamiltonian path would take a significant amount of time.…”
Section: Meta Path Searchmentioning
confidence: 99%
“…Connections exist only between infills that do not belong to the same sub-polygon (cluster) and are assigned with weights. The Hamiltonian search is basically NP-hard [35]. In the graphs presented, the computation of a Hamiltonian path would take a significant amount of time.…”
Section: Meta Path Searchmentioning
confidence: 99%
“…Dudek et al ( 2012 ) studied the existence of properly colored and rainbow Hamilton cycles in colored k-uniform complete hypergraphs, . Rahman et al ( 2014 ) presented a new degree based sufficient conditions for the existence of Hamiltonian paths in a graph. In 2015, Dudek and Ferrara ( 2015 ) revised the results proved by Dudek, Frieze, and Rucinski (2012) and showed that there is a constant such that every —bounded edge—colored contains a properly colored overlapping Hamilton cycle.…”
Section: Related Workmentioning
confidence: 99%
“…Although, Hamilton solved this particular puzzle, evaluation Hamiltonian cycles or paths in arbitrary graphs are proved expected among the hardest problems of information retrieval [1,2]. As a result, instead of complete characterization, most researchers aimed to find sufficient conditions for a graph to process a Hamiltonian cycle or path.…”
Section: Introductionmentioning
confidence: 99%